Enlightened Sexism, Structural Violence or the Failure of Representative Democracy: The 2016 Gender Equality Referendum - Bethell-Bennett, Ian A (International Journal of Bahamian Studies, 2016)
The Bahamas has a structure of inequality built into its colonial heritage and post-colonial governance. Women are not considered equal to men. In fact, many women do not see the need for equality. Some branches of the Church encourage the idea that women are less equal than men interpreting it as divine Christian law. Much like the divine right of kings, there is no challenging the doctrine. As the gender equality referendum failed once again after a 15-year gap between the vote in 2002 and the vote in 2016, can one be surprised. The failure of the referendum seems to speak to a distrust of government and a contempt for the political system, particularly in the wake of the gambling referendum, that was really an opinion poll, but, a poll that government refused to heed. The failure was also based on xenophobia, homophobia and clannishness. Enlightened Sexism seems to be an appropriate description of the policies and laws as well as attitudes of a large portion of the Bahamian population that agreed that women should not have the same rights as men.